Boycotted by parents (Journal of Parents and Teachers, 2014)
The article narrates the event described as xenophobic that took place in Baracaldo, when the parents of pupils at the "Juan Morejón" school refused to allow their children to attend if they had to share a classroom with 30 Moroccan pupils.This group of young people is mainly characterised by having fled violence and misery, while a group of parents decided to welcome them in a racist manner under the pretext of fear.
Keywords: Baracaldo; racism; xenophobia; social integration